Restatement on the origin and basis of the Malaysian legal system - Shuaib, Farid Sufian (2013)
The Federal Constitution is the basic document that provides the legal framework of Malaysia. In understanding Syariah courts, it is pertinent to examine the constitutional position of the courts. There is evidence of confusion in case law and scholarship writings regarding the issue for instance where some writers describing the Syariah courts as subordinate to civil courts. It is the proposition of this paper that such an examination will show that Syariah courts are parallel to civil courts. The constitutional position of Syariah courts is examined by referring to the Federal Constitution and case law and a doctrinal analysis of those materials is undertaken. The study on Syariah courts' position is essential to have a clear understanding its constitutional status and to facilitate any further study on possible improvement to the structure of Syariah courts.